PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN BAWANG MEKAH (Eleutherine Americana Merr.) TERHADAP KADAR MALONDIALDEHYDE TIKUS WISTAR (Rattus norvegicus) JANTAN PASCA PAPARAN ASAP ROKOK - Melda Mery Andiriyani; Eka Kartika Untari; Sri Wahdaningsih (Faculty of Pharmacy, Universitas Muslim Indonesia, 2014)
Malondialdehyde (MDA) is a biomarker of lipid peroxidation that is closely correlated with level of oxidative stress. The aim of this study was to know ethanol extract activities from E. americana leaves against blood plasma MDA in male Wistar rats exposed by cigarette smoke using tiobarbituric acid test. The simplicia extracted by maseration using 70% ethanol. Twenty four rats were divided into six groups, i.e. : a normal group, an exposed cigarette smoke (negative) control group, a positive control group and three treatment groups. One normal group received carboxyl methyl cellulose and another groups exposed cigarette smoke during 14 days. Positive control group received vitamin E (18mg/kg BW), and another groups received ethanol extract of E. americana leaves doses 180; 90; 45mg/kg BW, respectively. The MDA level was analysed by spectrophotometer UV-Visible in 532,2 nm. The MDA level statically analysis by Kruskal-Wallis test and following by Mann-Whitney test. The mean MDA levels of normal group, negative control group, positive control group and groups received ethanol extract of E. americana leaves doses 180; 90; 45mg/kg BW were 0,11±0,09; 13,74±2,84; 0,06±0,03; 10,88±2,19; 0,13±0,03; 0,03±0,02 ppm. The mean MDA levels of groups received ethanol extract of E. americana leaves doses at 180; 90mg/kg BW significantly (p<0,05) lower than negative control group. These results show the beneficial effect of ethanol extract of E. americana leaves in the MDA level reducing on the rats that exposed by cigarette.